O meme é a mensagem: cultura memética, entretenimento digital e estética remix na cultura participativa - Inocêncio, Luana Ellen de Sales (2015)
As a kind of post-modern folklore, internet memes are artifacts of digital culture, elaborated by interactors that resignify everyday matters, media content and sociopolitical discourses through humor. By observing how this process takes place, this research aims to question the heavy flow of amateur audiovisual culture, guided by memetic reappropriation, that the interactors produce and disseminate as entertainment, articulating a known theoretical framework of cyberculture, looking for new hypotheses for the phenomenon. In this sense, the objective of this study is to investigate how the creative reinterpretation of audiovisual content - using editing softwares to create parodies, remixes or mashups - allows the collective structure of a playful experience of consumption and interpretation of cultural products. To this end, is conducted a mapping of genres of memetic language, seeking categorize them from a taxonomy for identifying its peculiarities, its modes of symbolic construction, synthesis and reinterpretation in their plastic and sensitive interfaces. The research aims to observe the interactionals, cognitives and sociability relations implied in this process, in which from a set of terms and references, a specific imaginary is recognized and intensely experienced by interactors, being a rich sample of intimacy with his fans and his diegetic universe. As an articulating element of this investigation, memes created and shared from two major media events will be analyzed, the Oscar 2014 and the Grammy in 2015, seeking to understand how the entertainment industry potentiates the discursive fan-viewer immersion in these events, by the chaining of catalysing performances of memes and targeted speeches, guided by elements that reconfigure the media experience of the pop culture fan-spectator.